The adaptation of Australian community disaster resilience scorecard & self-assessment of community disaster resilience (Cdr): Kelantan's flood affected communities - Mohamed Ludin, Salizar (2016)
INTRODUCTION: Community disaster resilience is the community abilities to adapt to the changes at their living place caused by any hazards exposure using its own personal and environmental resources. This concept is very important for the individual, social groups or social-ecological system to absorb, withstands, live with and accommodate disturbances and it can be an important link between social cohesion and resilience. In the face of the need for Malaysia to re-look and develop the country’s sustainable disaster recovery policies and rebuilding post-disaster, the level and how to measure our community disaster resilience and the impact of social cohesiveness is unknown.